2015
DOI: 10.1002/jbm.b.33534
|View full text |Cite
|
Sign up to set email alerts
|

In vitro bioactivity study of TiCaPCO(N) and Ag‐doped TiCaPCO(N) films in simulated body fluid

Abstract: Bioactivity of multicomponent TiCaPCO(N) and Ag-doped TiCaPCO(N) films was evaluated in vitro using simulated body fluid (SBF) and compared with that of bioactive glass Biogran. The first group of films was fabricated by magnetron sputtering of composite TiС -Ti PO -CaO target produced via the self-propagating high-temperature synthesis (SHS) method (TiCaPCON films), after which their surface was implanted with Ag ions to obtain Ag-doped TiCaPCON films. The second group of films was fabricated by pulsed electr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 67 publications
(139 reference statements)
0
8
0
Order By: Relevance
“…The coating material with both antimicrobial activity and biocompatibility is important and leads to enhancement of the probability of implant success [ 9 ]. The following functionalization strategies have already been applied to increase antibacterial potential: drug-loaded surfaces [ 10 ], silver-implanted surfaces [ 11 ], polymer-functionalized surfaces [ 12 ], anodized/oxidized/ion-implanted surfaces [ 13 , 14 ], UV-activated surfaces [ 15 ], nanoscale surfaces [ 16 ], etc. A systematic review by J. Grischke et al concluded that highly modified surfaces enhance antimicrobial activity compared to that of commercial, pure titanium [ 8 ], but some research proved the significant cell toxicity of these surfaces [ 17 , 18 ], which limits the clinical application of new surfaces.…”
Section: Introductionmentioning
confidence: 99%
“…The coating material with both antimicrobial activity and biocompatibility is important and leads to enhancement of the probability of implant success [ 9 ]. The following functionalization strategies have already been applied to increase antibacterial potential: drug-loaded surfaces [ 10 ], silver-implanted surfaces [ 11 ], polymer-functionalized surfaces [ 12 ], anodized/oxidized/ion-implanted surfaces [ 13 , 14 ], UV-activated surfaces [ 15 ], nanoscale surfaces [ 16 ], etc. A systematic review by J. Grischke et al concluded that highly modified surfaces enhance antimicrobial activity compared to that of commercial, pure titanium [ 8 ], but some research proved the significant cell toxicity of these surfaces [ 17 , 18 ], which limits the clinical application of new surfaces.…”
Section: Introductionmentioning
confidence: 99%
“…The obtained results agree well with those previously reported for multicomponent TiCaPCON-based bioactive surfaces. 54 …”
Section: Resultsmentioning
confidence: 99%
“…Nevertheless, the ESA method has a number of disadvantages, such as a high content of structural defects (pores, microcracks) [8], high level of surface roughness [9], in some cases, contamination by oxygen (for example, if the process was conducted in an air environment), and the presence of substrate matter in the coating composition [10].…”
Section: Introductionmentioning
confidence: 99%